Inedxing as Problem Solving: A Cognitive Approach to Consistency - David, C.; Giroux, L.; Bertrand-Gastaldy, S.; Lanteigne, D. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Indexers differ in their judgment as to which terms reflect adequately the content of a document. Studies on interindexers' consistency identified several factors associated with low consistency, but failed to provide a comprehensive model of this phenomenon. Our research applies theories and methods from cognitive psychology to the study of indexing behavior. From a theoritical standpoint, indexing is considered as a problem solving situation. To access to the cognitive processes of indexers, three kinds of verbal reports are used. We will present results of an experiment in which four experienced indexers indexed the same documents. It will be shown that the three kinds of verbal reports provide complementary data on strategic behavior, and that it is of prime importance to consider the indexing task as an ill-defined problem, where the solution is partly defined by the indexer him(her)self. Résumé: Afin de mieux cerner l'origine des différences relevées par les études sur la cohérence inter-indexeurs, nous adjoignons les théories et méthodes issues de la psychologie cognitive (spécifiquement celles qui considèrent une tâche comme une situation de résolution de problème) à l'étude des processuscognitifs impliqués lors de l'indexation. Cette approche permet d'identifier les stratégies cognitives élaborées et utilisées par les indexeurs. Afin d'avoir accès à leurs processus cognitifs, trois types de verbalisations sont recueillis. Nous présenterons les résultats d'une expérimentation pour laquelle quatre indexeurs expérimentés ont analysé les mêmes documents. Les résultats avancés démontreront la complémentarité des données issues des trois types de verbalisations et l'importance de considérer l'indexation en tant que problème mal- défini; la solution étant définie en partie par l'indexeur.